The Relationship between Addiction to Massively Multiplayer Online Role-Player Games and the Sleep Quality of Students in Higher Education - Safitri, Desy; Ambarwati, K. Diah (Bisma The Journal of Counseling, 2024)
Online games addiction creates a desire to continue repeating these activities. Staring at or using a cellphone for too long while playing online games can result in poor sleep quality which will have an impact on a person's physiological and psychological health. This study aims to analyze the relationship between Massively Multiplayer Online Role-Player Games (MMORPG) online game addiction and sleep quality in students. This research used quantitative correlational methods with subjects of 90 people addicted to MMORPG online games at several universities in Indonesia. The sample was selected using non-probability sampling techniques. Data collection was carried out using a questionnaire measuring online game playing and sleep quality. Next, the data was analyzed using Pearson Product Moment correlation assisted by the Statistical Packages for Social Sciences (SPSS) 25 computer program. The results showed that the highest level of online game addiction was moderate level at 70 respondents (77.8%) and the highest quality of sleep was Poor sleep quality was 86 respondents (95.6%).  It can be concluded that there is a significant negative relationship between MMORPG online game addiction and sleep quality in students. The latest information in this research has implications for efforts to overcome the negative effects of online game addiction on the physiological and psychological health of students.